Acute and chronic states due to hallucinogenic substance consumption and treatment strategies - Öztürk, Özgür; Genç, Yasin; Odabaşıoğlu, Gürkan; Beyazyürek, Mansur (Journal of Dependence, 2007)
Hallucinogens which are also named as psychomimetics and psychodelics are substances whose consumption cause hallucinations, delusions and illusions. They can be synthtetic or may be found naturally. LSD (lysergic acid dietylamide) is a prototype of classical synthetic halucinogens which was firstly synthesized in 1938 by Albert Hoffman . They are generally consumed orally because of high rate of absorption by this way. Tolerance to hallucinogens also begins very rapidly, thus, they are very rarley used over once or twice a week. Mentioning most typical of hallucinogens, LSD, behavioral effects begin within a hour and reaches its peak effect in 2-4 hours . After 10-12 hours , patient gets back to hallucinogen free status with some dysphoria and fatigue. Autonomic signs like piloerection, mydriazis, hyperreflexia , hypertension, hyperthermia may also be seen with halucinogens. Cross tolerence among different halucinogenic drugs also occur. Psychopharmacologically, the hallucinogenic effect of these drugs are related to decreased serotonine turn over in brain. 5HT2 a receptor antagonists can inhibit the hallucinogenic effect . The lethal dose for humans is not known but generally considere as high. Deaths from hallucinogen abuse generally happen by accidents according to misperceptions during hallucinations. Magical thinking after chronic hallucinogen consumption may cause personality disorders especially among adolescents resulting with social withdrawal symptoms. Long term psychotherapy is indicated in such patients.